2008
DOI: 10.1136/jmg.2007.054676
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early FXTAS motor symptoms using the CATSYS computerised neuromotor test battery

Abstract: Background-Carriers of the FMR1 premutation allele are at a significantly increased risk for a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
6
19
2
Order By: Relevance
“…This may be an indicator for a specific female subtype of impairment. A study by Loesch (2015) showed a relationship of severity of psychiatric symptoms in female premutation carriers dependent on a non-linear effect of CGG repeat size within the premutation range, similar to the severity of FXPOI symptoms (Allen et al, 2008; Hunsaker et al, 2011; Sullivan et al, 2005) and previous reports of psychopathology in female carriers (Roberts et al, 2009; Seltzer, Barker, et al, 2012). The mid-range CGG repeat size is associated with an increased severity of symptoms in these studies.…”
Section: Discussionsupporting
confidence: 68%
“…This may be an indicator for a specific female subtype of impairment. A study by Loesch (2015) showed a relationship of severity of psychiatric symptoms in female premutation carriers dependent on a non-linear effect of CGG repeat size within the premutation range, similar to the severity of FXPOI symptoms (Allen et al, 2008; Hunsaker et al, 2011; Sullivan et al, 2005) and previous reports of psychopathology in female carriers (Roberts et al, 2009; Seltzer, Barker, et al, 2012). The mid-range CGG repeat size is associated with an increased severity of symptoms in these studies.…”
Section: Discussionsupporting
confidence: 68%
“…66 CATSYS was selected as it had been previously used in premutation carriers; also, a recent study showed CATSYS measurements to be associated with clinician-rated UPDRS items assessing tremor and bradykinesia. 53,54,67 Future studies could include UPDRS in the protocol, to complement the CATSYS.…”
Section: Discussionmentioning
confidence: 99%
“…42 CATSYS has been previously used in premutation carriers. 53,54 The SCID was customized prior to initiating this study to include the modules for mood, anxiety, substance use, somatoform and adjustment disorders and the screening questions for psychotic symptoms. Additionally, dementia and cognitive disorder not otherwise specified (NOS) were diagnosed through interview according to the DSM-IV TR criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The Coordination-Tremor-Balance Test System was used to assess SC’s tremor and balance (Table 1). 12,13 SC showed impairment in the tremor and maximum frequency assessments. 14 She also showed significant balance problems, falling within the higher range of the FXTAS group for the sway task.…”
Section: Case Reportmentioning
confidence: 89%